PENGARUH GAYA KEPEMIMPINAN, LOCUS OF CONTROL TERHADAP KINERJA INTERNAL AUDITOR (PENELITIAN PADA PT. BANK SULUT DAN PT. BNI, TBK) - Mogi, Aileen Janet; Pangemanan, Sifrid (ACCOUNTABILITY, 2013)
In facing the environment change, a company should level up the effectiveness of management control to achieve the final goal between the individual and the organization. That is why a leader should be able to motivate the subordinates so the goal can be achieved.  Besides leadership style, locus of control also affects the internal auditor performance. Internal Auditor performance is one of the important indicators to reach the banking company success that is the reason why the researcher is interested with the title of this final task.This research is aimed to know the influence of leadership style and locus of control on the internal auditor performance. This research was done at 2  ( two)  banking companies, those are PT. Bank SULUT and PT. BNI, Tbk. In this research the independent variable  ( X )  are the leadership style  ( X1 )  and locus of control ( X ) ; meanwhile the dependent variable  ( Y )  is performance  ( Y ) . The data collection method used is through survey and questioner with a list of questions. It would be answered by the respondents and those are the internal auditors.  The technique used in data analysis to test the hypothesis was done by using the double linear regression analysis and processed through SPSS program Version 19.0. The result shows that the leadership style partially does not have an effect on the performance of internal auditor but the locus of control has an effect on the internal auditor performance. But simultaneously, the leadership style and locus of control influence the performance of internal auditor.2Key words: Leadership style, Locus of control, and The Performance of Internal Auditor.